The Role of Posters Written in Indigenous Languages in Disseminating Health-Awareness Information within the Far North Region of Cameroon - James N. Tasah (European Scientific Journal, ESJ, 2021)
It is an established fact that the majority of the illiterate population in Cameroon, in general, and in the Far North Region in particular are excluded from life-saving information because of illiteracy. Since all important information is usually communicated only in official languages, most illiterate men and women are not only ignorant of vital information on different issues affecting their lives, but are also vulnerable to diseases. This paper posits that combating health epidemics is more effective through the use of imageassociated sensitization posters written in minority languages than through sensitization messages transmitted through official languages. It argues that posters written in indigenous languages are not only culturally relevant and well accepted by community members, but also enhance and facilitate respondents’ understanding of health issues. The findings from this work obtained through the administration of questionnaires revealed that the percentages of the illiterate respondents who understand image-based posters in the MT is significantly higher than those who claimed to understand imagebased posters in French. On the basis of the findings, the government and NonGovernmental Organizations (NGOs) are strongly encouraged to ensure that important health-related information should be presented in picture-based posters, flyers or brochures in the MT.